Distributive health literacy and medication management: A longitudinal qualitative study with Bhutanese former refugees in Tasmania. (6th June 2021) - Murray, Linda; Elmer, Shandell; Breen, Juanita; Nash, Rosie
Abstract: Issue addressed: Tasmania, Australia is home to a population of Bhutanese former refugees who have resettled since 2007. Their refugee journey and disrupted education opportunities have resulted in gaps in literacy in their primary language (Nepali), and many suffer one or more chronic conditions (ongoing communicable or noncommunicable diseases (NCDs)). This research explored how this community perceives chronic conditions and managed their medication using the concept of distributed health literacy. Methods: A longitudinal qualitative method was used whereby 15 former refugees and their carers were interviewed 3‐4 times over 9 months. Data were thematically analysed using a hybrid approach of inductive and deductive coding and theme development. Results: Four themes related to distributed health literacy were identified. These were "barriers to medication literacy and adherence, " "support people as health literacy mediators, " "understandings of chronic disease" and "strengthening distributed health literacy." Participants described managing relatively low levels of knowledge about their chronic conditions and medications by appointing support people who acted as health literacy mediators. This resulted in interactions with health professionals, information gathering and medication use being enacted collectively between family members. Carers felt responsible for supporting others who were new to the Australian health system to learn new skills in addition to assisting with tasks such as informal interpreting. So what?: Interventions to improve the health literacy of former refugees should focus on collective critical health literacy action rather than just the functional health literacy of individuals. Health literacy mediators are a vital form of support for former refugees managing chronic conditions, so must be included in education and support programs.